The Genealogy of Contemporary Leadership: A Cadre-Building Model in Pesantren Educational Institutions - Sukatin, Sukatin; Safitri, Lidya (Development: Studies in Educational Management and Leadership, 2025)
This study investigates the genealogy of contemporary leadership through the implementation of a transformational leadership-based cadre-building model within the context of Islamic education management in pesantren (Islamic boarding schools). Pesantren, as traditional educational institutions rich in noble values, face modernization demands that necessitate leadership adaptation without compromising their cultural and spiritual identity. Utilizing a descriptive qualitative survey approach with a case study at Pondok Modern Daarul Ikrom, Lampung, this study thoroughly analyzes how pesantren leaders systematically cultivate future leaders through a structured cadre-building process. The findings indicate that transformational leadership, manifested through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, serves as a pivotal element in fostering a shared vision, developing individual potential, and enhancing the quality of human resources within pesantren. The implementation of this leadership style effectively establishes a cadre-building system that harmoniously balances the pesantren's foundational values with contemporary adaptation demands. This study contributes to the literature on Islamic education management by offering a nuanced understanding of adaptive and strategic leadership dynamics crucial for maintaining the relevance and sustainability of religious educational institutions in the modern era.